Sustainable development key to limiting climate change-driven wildfire damages - Yi-Ling Hwong; Edward Byers; Michaela Werning; Yann Quilcaille (Environmental Research: Climate)
Climate change is causing wildfires to become more frequent and intense. While predicting burned areas using bioclimatic and anthropogenic factors is an active research area, few studies have examined what drives the economic damages of wildfires. Our study aims to fill this gap by analyzing key factors influencing global economic wildfire damages and projecting future damages under three shared socioeconomic pathways (SSPs). We apply regression analyses to identify significant predictors of economic wildfire damages at country levels and use the fitted model to project future damages under SSP126, SSP245, and SSP370. Results show that the human vulnerability index (HVI), reflecting socioeconomic conditions, is the strongest predictor of historical wildfire damages, followed by water vapor pressure deficit during the fire season and population density around forested areas. We found high population density to be associated with lower damages. These findings contrast with studies of burned areas, where climate factors are more dominant. Our model projects that by 2070, average global economic wildfire damages will be three times higher under SSP370 than SSP126. Our model also shows that following SSP126 not only reduces wildfire damages but also lessens the inequalities in damage distribution across countries. This pathway’s dual focus on equitable socioeconomic progress and climate action potentially enhances a country’s resilience that helps mitigate wildfire damages. Our analyses also indicate that strong socioeconomic development can offset wildfire damages associated with climate hazards, although this is less certain under SSP370. SSP126’s integrated approach improves both socioeconomic conditions and limits global warming, providing substantial benefits to less developed countries while still reducing damages in developed nations, despite their already low HVI scores. Our work complements existing research on burned areas and underscores the importance of sustainable development and international collaboration in reducing the economic damages of wildfires.